"One Stone Two Birds" Design for Dual‐Functional TiO2‐TiN Heterostructures Enabled Dendrite‐Free and Kinetics‐Enhanced Lithium–Sulfur Batteries. Issue 18 (16th March 2022) - Xue, Pan; Zhu, Kaiping; Gong, Wenbin; Pu, Jun; Li, Xiyao; Guo, Can; Wu, Liyun; Wang, Ran; Li, Hongpeng; Sun, Jingyu; Hong, Guo; Zhang, Qiang; et al.
Abstract: Lithium–sulfur batteries (LSBs) are regarded as promising next‐generation energy storage systems owing to their remarkable theoretical energy density (2600 Wh kg ‐1 ) and low cost. However, sluggish electrochemical kinetics, lithium polysulfides (LiPS) shuttling, and uncontrollable Li dendrite growth seriously hamper the commercial application of LSBs. Herein, dual‐functional 3D interconnected free‐standing fibers embedded with TiO2 ‐TiN heterostructures as an advanced skeleton are designed for concurrently regulating both the sulfur cathode (S/hollow TiO2 ‐TiN) and Li anode (Li/solid TiO2 ‐TiN). As a cathode skeleton, the hollow TiO2 ‐TiN fibers afford synergistic functions of chemical anchoring, physical confinement, and excellent electrocatalysis for LiPS. Meanwhile, the multifunctional skeleton with remarkable lithiophilicity and high conductivity can accomplish uniform Li deposition and homogeneous Li ion flux for inhibiting the growth of dendrites. Benefiting from these advantages, the full battery (S/hollow TiO2 ‐TiN || Li/solid TiO2 ‐TiN) exhibits excellent electrochemical performance, including high cycling stability (988.8 mAh g −1 after 200 cycles at 0.5 C) and impressive rate properties (639.3 mAh g −1 at 2 C). This work inaugurates a novel strategy from experimental and theoretical aspects for fabricating LSBs with robust electrochemical performance. Abstract : Dual‐functional TiO2 ‐TiN heterostructure fibers are developed for concurrently regulating both the S cathode and Li anode. The dual‐functional fiber host not only catalyzes the transformation of lithium polysulfides, but also realizes uniform Li deposition, making it of great potential for applications in high‐performance lithium–sulfur batteries.